Viscosity modelling of chlorinated brines in three-component systems with a continuously variable temperature range between 293-323 K - Andrés Soto-Bubert; Rashmi Bhardwaj; Satheeshkumar Rajendran; Roberto Acevedo (Chemical Thermodynamics and Thermal Analysis)
The paper proposes a semi-empirical model to determine the viscosity in units of mil Pas of chlorinated brines in the concentration range between 0 and 4 molal and with a temperature range between 293 and 323 K. A continuous viscosity function is proposed for ''η'' the form where η[m1,m2,T] and ''m1'' and ''m2'' correspond to the molal concentrations of the chlorinated salts dissolved in aqueous solution (1) and (2) respectively and ''T'' ''is the temperature in Kelvin. The proposed model is a variant of a model published in 2020 in Scientific Reports by Hazim Qiblawey et al..Our proposal's benefits are that it has an error equivalent to the data reported in the literature. Temperature is treated as a continuous function to estimate viscosity, unlike the model of the equation of Hazim Qiblawey and workers working with temperatures discrete by proposing an adjustment for each temperature. The ternary study systems are NaCl−CaCl2−H2O and KCl−CaCl2−H2O to create a continuous function in compositions and temperature to calculate viscosities achieving error adjustments (%AAD) of around 1 %. Overall, the development of a new and refined model for viscosity in chlorinated brines in three-component systems, as presented in the current article, can be seen as a valuable contribution to the mining sector, offering potential benefits in terms of process optimization, resource utilization, and operational efficiency.